2020
DOI: 10.17081/invinno.8.2.3639
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de simulación de eventos discretos para el análisis y mejora del proceso de atención al cliente

Abstract: Objetivo: Diseñar y desarrollar un modelo de simulación de eventos discretos para el proceso de atención del cliente de una Pyme dedicada al negocio de la comida rápida con el fin de conducir experimentos direccionados a comprender el comportamiento del sistema y evaluar estrategias de optimización. Metodología: El procedimiento se clasifica en cuatro etapas: (I) Análisis de la empresa y definición del problema, (II) Descripción de procesos y contextualización de un modelo, (III) Generación del modelo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Another feature is the technology used in platforms for sending field data. It was found that other authors mostly use modules in ISM free band [9,11,26,13,14,15,16,21,23,24,25], due to their low energy consumption capacity and portability. This project evaluated the protocol and technology suitable for this application, which has led to the choice of LoRa technology, which is used in other specific projects for sending data due to its scope for applications in rural areas [11,15,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another feature is the technology used in platforms for sending field data. It was found that other authors mostly use modules in ISM free band [9,11,26,13,14,15,16,21,23,24,25], due to their low energy consumption capacity and portability. This project evaluated the protocol and technology suitable for this application, which has led to the choice of LoRa technology, which is used in other specific projects for sending data due to its scope for applications in rural areas [11,15,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…These projects involve data collection from temperature, humidity, or rainfall sensors around the crop area for decision making [13,20], as well as applications where there is an infrastructure to control the opening or closing of field valves, based on the information collected from the following projects [9,10,23,24,25,26,11,12,14,15,16,19,21,22]. The designed system was based on several of the previous initiatives, taking different features and involving not only data collection, but also the interaction between Human-Machine, in order to have a more comfortable relationship between the producer and his/her crop.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants who took part in the test are directly related to the jurisprudence environment. They were lawyers, who had carried out jurisprudential consultations in the last week [19,20,21]. The participants were assigned diverse topics such as "Habeas data" or "resignation".…”
Section: Test Applicationmentioning
confidence: 99%